A new species of Metriocnemus van der Wulp (Diptera: Chironomidae) with a tentative phylogeny of the genus - Donato, Mariano Humberto (2010)
The male and female of the new species Metriocnemus puna sp. n from the Argentinean Puna are described and illustrated. A parsimony analysis including 24 well-described species of the genus plus the new species based on the adult male was conducted in order to access the phylogenetic position of the new species and to provide the first phylogenetic hypothesis for the genus.